An Analysis of Extendibility and Early Termination Provisions: The Importance of Framing Duration Safeguards - Weber, Libby; Mayer, Kyle J.; Macher, Jeffrey T. (Academy of Management Journal, 2011)
We augment transaction cost economics with social cognitive psychology to show that contract framing is an important element in minimizing issues in focal exchanges and managing buyer-supplier relationships. We find that exchange partners use promotion-framed extendibility clauses to address contract duration in the presence of greater physical distance, measurement difficulty, prior relationships in other businesses, and reusable technology. Our results suggest that contracts not only protect against exchange hazards, but also function as relationship management tools.